Dwyer–Kan homotopy theory for cyclic operads. Issue 1 (14th February 2021) - Drummond-Cole, Gabriel C.; Hackney, Philip
Abstract: We introduce a general definition for coloured cyclic operads over a symmetric monoidal ground category, which has several appealing features. The forgetful functor from coloured cyclic operads to coloured operads has both adjoints, each of which is relatively simple. Explicit formulae for these adjoints allow us to lift the Cisinski–Moerdijk model structure on the category of coloured operads enriched in simplicial sets to the category of coloured cyclic operads enriched in simplicial sets.